Safety and Pharmacokinetics of a Tenofovir Alafenamide Fumarate-Emtricitabine based Oral Antiretroviral Regimen for Prevention of HIV Acquisition in Women: A Randomized Controlled Trial. (June 2021) - Thurman, Andrea R.; Schwartz, Jill L.; Cottrell, Mackenzie L.; Brache, Vivian; Chen, Beatrice A.; Cochón, Leila; Ju, Susan; McGowan, Ian; Rooney, James F.; McCallister, Scott; Doncel, Gustavo F.
Abstract: Background: Daily oral emtricitabine (FTC, F)/tenofovir disoproxil fumarate (TDF) combination is approved for HIV pre-exposure prophylaxis (PrEP) in men and women. Tenofovir alafenamide fumarate (TAF) is a newer, more potent prodrug of tenofovir (TFV), and in combination with FTC, has recently been approved for prevention of HIV through rectal transmission. Methods: This Phase I, prospective, interventional, randomized study was conducted in three clinical sites: PROFAMILIA, Santo Domingo, Dominican Republic; University of Pittsburgh and Eastern Virginia Medical School. We assessed the multi-compartmental pharmacokinetics (primary outcome) and safety (secondary outcome) among HIV uninfected women randomized to F/TDF (200mg/300mg) or F/TAF (200mg/25mg; F/TAF25) (n=24) in a single dose phase (SDP) and F/TDF, F/TAF (200mg/10mg; F/TAF10), or F/TAF25 (n=75) in a multiple dose (14 daily doses) phase (MDP). We described PK parameters in plasma, peripheral blood mononuclear cells (PBMCs), and cervicovaginal (CV) and rectal fluids and tissues. ClinicalTrials.gov #NCT02904369, completed. Findings: Recruitment for the study began on 5 October 2016. The first participant was enrolled on 6 October 2016 and the last participant completed the study 21 November 2017. Plasma: TFV concentrations area under curve (AUC) were ~20 fold lower following F/TAF versus F/TDF. TFV-diphosphate (TFV-DP) AUC concentrations in PBMCs were 7-fold higher with F/TAF25 versus F/TDF. Median TFV-DP concentrations in vaginal tissue (4hours post last dose) were approximately 6-fold higher with F/TAF25 versus F/TDF. TFV and TFV-DP were lower with F/TAF versus F/TDF in rectal tissue. Concentrations of FTC and FTC-triphosphate (FTC-TP) were similar across matrices and treatment arms. Gastrointestinal adverse events (AEs) occurred more frequently in F/TDF users (44.0%) than in either F/TAF group (11.5 and 12.0%). Interpretation: F/TAF was safe and well-tolerated. TFV-DP concentrations were higher in PBMCs and similar or higher (4h post dose) in female genital tract tissues for F/TAF versus F/TDF. High FTC and FTC-TP concentrations in all compartments support the potential of F/TAF as a new PrEP combination for women. Funding: United States Agency for International Development (USAID)/the President's Emergency Plan for AIDS Relief (PEPFAR) through Cooperative Agreement AID-OAA-A-14-00011 with CONRAD/Eastern Virginia Medical School. This publication resulted in part from research supported by the University of North Carolina at Chapel Hill Center for AIDS Research (CFAR).